2018
DOI: 10.1186/s40709-017-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of cultivated Korarima [Aframomum corrorima (Braun) P.C.M. Jansen] populations from southwestern Ethiopia using inter simple sequence repeats (ISSR) marker

Abstract: BackgroundKorarima (Aframomum corrorima) is a perennial and aromatic herb native and widely distributed in southwestern Ethiopia. It is known for its fine flavor as a spice in various Ethiopian traditional dishes. Few molecular studies have been performed on this species so far. In the present paper, the ISSR technique was employed to study the genetic diversity in populations of cultivated A. corrorima.ResultsSeven ISSR primers produced a total of 86 clearly scorable DNA bands. High levels of genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Like the present study a high and signi cant within populations genetic variations have been reported in previous studies using ISSR markers. In line with this, Dagmawit and Bekele [32] reported high (72.53%) within population genetic variation with only 27.47% for the among populations genetic variation for Korarima populations of Ethiopia using seven ISSR markers. Likewise, Hailu et al [16] reported high (64.8%) intra-population variations with lower (34.2%) inter-population variations for Korarima populations using ISSR markers.…”
Section: Population Genetic Structure and Gene Owsupporting
confidence: 56%
“…Like the present study a high and signi cant within populations genetic variations have been reported in previous studies using ISSR markers. In line with this, Dagmawit and Bekele [32] reported high (72.53%) within population genetic variation with only 27.47% for the among populations genetic variation for Korarima populations of Ethiopia using seven ISSR markers. Likewise, Hailu et al [16] reported high (64.8%) intra-population variations with lower (34.2%) inter-population variations for Korarima populations using ISSR markers.…”
Section: Population Genetic Structure and Gene Owsupporting
confidence: 56%
“…The success of a crop improvement program highly depends on the availability and knowledge of the genetic resources in a germplasm collection [32]. Since areas of high genetic diversity mostly contribute more accessions than those of low diversity for further and future collection, breeding and conservation activities should be based in areas with high genetic diversity.…”
Section: Population Genetic Diversitymentioning
confidence: 99%
“…ISSR, as a modification of SSRs, offers such advantages such as high reproducibility, high polymorphism, low DNA requirements, easy handling, and high genomic distribution [31]. Chombe and Bekele [32] investigated the genetic diversity in populations of Aframomum corrorima (an economically important medicinal plant in Ethiopia) via seven ISSR primers. Moreover, Hashemifar and Rahimmalek [33] also reported that ISSR markers showed high efficiency in the evaluation of population diversity in Perovskia.…”
Section: Ssr and Issrmentioning
confidence: 99%